PENGARUH PENGUMPULAN, PENDISTRIBUSIAN DAN PENDAYAGUNAAN ZAKAT TERHADAP EFEKTIVITAS MANAJEMEN ZAKAT DI BADAN AMIL ZAKAT DAERAH SUMATERA UTARA - Novi Indriyani Sitepu (Universitas Islam Negeri Sumatera Utara, 2015)
Substantively, zakat, alms andinfaq is part of the core of the religious spirit of the mechanisms of redistributing income. Zakat funds drawn from the wealth of redundant and distributed to those in need. In connection with the collection of zakat, although still very much with national potential but continued to show a significant rise. For the case of North Sumatra public confidence in the Bazda-SU still to fluctuation. This study tested how Influence Collection, Distribution and Utilization of Zakat to the Zakat Management Effectiveness in BadanAmil Zakat North Sumatra. The study was conducted by using the technique of multiple regression analysis of the 67 survey respondents. The results showed that the variable collection of zakat (P1) is positive and significant effect on the effectiveness of management in Amil Zakat North Sumatra with a value of 4.996 tcount>ttable 2.000. Variable P2 (zakat distribution) effect on the effectiveness of management in BadanAmil Zakat North Sumatra. It is known from the test where tcount of 3.826 and P3 variable (utilization of zakat) effect on the effectiveness of the management of 2,947 tcount Based on Ftest concluded that the better the pattern of the collection, distribution and utilization of zakat is used, the better the effectiveness of the management of zakat The Bazda North Sumatra.